Management Effects on Soil Organic Carbon Stock in Mediterranean Open Rangelands—Treeless Grasslands - Parras‐Alcántara, Luis; Díaz‐Jaimes, Luisa; Lozano‐García, Beatriz (Land degradation & development, 2015)
Soil organic carbon (SOC) is subject to relatively rapid changes. In grasslands soils, the management system influences these changes. Therefore, these soils play a crucial role in climate change mitigation. Current research has developed strategies and methodologies to help us understand their role as a carbon sink. In this study, the SOC and total nitrogen contents and stocks (SOC‐S) and their variation with depth were evaluated in annual crop rotations (cereal–fallow). Fifty soil profiles were sampled in the Los Pedroches Valley (southern Spain). This area consists of Mediterranean open rangelands—treeless grasslands with cereal–fallow rotation, under two management systems: long‐term (20 years) organic farming (OF) and conventional tillage (CT). The studied soils were Cambisols (CM), Leptosols (LP) and Luvisols (LV). The objective of this research was to determine any management system effects (OF vs CT) on SOC and total nitrogen contents and stocks and their variation with profile depth. It was observed that SOC concentration decreased with depth (Ah–Ap > Bw > C). The SOC concentration was higher in the top soil for all studied soils in OF compared with CT. The highest totals of SOC‐S were found in LV‐OF (66·01 Mg ha⁻¹) and the lowest in LP‐CT (21·33 Mg ha⁻¹). Significant differences (p < 0·05) between soils types and management practices were found in carbon stocks, increasing the SOC‐S in OF compared with that in CT in all studied soils; this increase was 75·25%, 85·73% and 234·88% for CM, LV and LP, respectively. The results indicated that management practices significantly influence SOC‐S in the Los Pedroches Valley and, consequently, OF in annual crop rotations (cereal–fallow) is an excellent alternative to CT that increases the SOC content in Mediterranean open rangelands—treeless grasslands environments. Copyright © 2013 John Wiley & Sons, Ltd.